DELAPAN BELAS TAHUN PERKEMBANGAN PENELITIAN SUSTAINABILITY REPORT: STUDI LITERATUR REVIEW - Bima, Muhammad; Indah Setiawan, Rhisma; Apriliana Agustin, Dwi; Djasuli, Mohamad (Jurnal GeoEkonomi, 2024)
This study aims to examine the development of research related to sustainability report in the international scope. The review is based on 59 articles that discuss published in Scopus indexed scientific journals (Q1 and Q2). Articles were selected with the keyword "sustainability report" which was traced in the "article title" only. Article mapping includes journal name, year of publication, research methods, research variables, and data sources. research variables, and research data sources. This study found that the development of research on sustainability reports tends to increase from year to year and the most occurred in 2019. The publication of the most sustainability report articles in the Journal of Cleaner Production journal. Research articles related to sustainability report mostly uses qualitative methods and secondary data sources. Research with quantitative methods more often use the variables Return on assets (ROA), Level of indebtedness (Leverage), and Firm size. of indebtedness (Leverage), and Firm size. This study provides evidence of the development of sustainability report research that has been published in accredited international scientific journals (Q1 and Q2).